Review. Specific detection of Listeria monocytogenes in foods using comercial methods: from chromogenic media to real-time PCR - Janzten, M.M.=700 1 Navas, J.J.; Corujo, A.; Moreno, R.; Lopez, V.; Martinez Suarez, J.V.
(Es, En)
ilus., 80 ref.
Keywords: LISTERIA MONOCYTOGENES; BACTERIA; ALIMENTOS; LISTERIOSIS; ENFERMEDADES INFECCIOSAS; ENFERMEDADES TRANSMITIDAS POR ALIMENTOS; HOMBRE; SALUD PUBLICA; ESPAÑA